Information and Communication Technologies for Development: The Bottom of the Pyramid Model in Practice - Renee Kuriyan and Isha Ray Kentaro Toyama (The Information Society, 24: 93-104, 2008, 2008)
The currently influential model for information and communication technologies for development (ICT4D) is based on increasing the well-being of the poor through market-based solutions, and by using low-cost but advanced technologies. Using ethnographic methods, we chart out the contradictions that could arise when sucha development-through-entrepreneurship model is implemented. We examine the Akshaya project, a franchise of computer-service kiosks in Kerala, India, which strives simultaneously for social development through access to computers and financial viability through cost recovery and entrepreneurship. We show that tensions within the state and among entrepreneurs and perceptions of public versus private among consumers make it challenging to meet the twin goals of commercial profitability and social development